PERAN MANAJER YANG BERMANFAAT DALAM MENINGKATKAN KINERJA PERUSAHAAN - Yulfiswandi; Brillian, Ahmad; Zetty Aqmi, Alifia Lisda; Melina, Bonita; Fortuna, Dewi (Universitas Putera Batam, 2024)
In the current era of digitalization and globalization, the role of managers is growing in managing the increasing information technology risks in modern banking. In addition, managers also play an important role in internal and external communication. This research was conducted with the aim of knowing the role of managers in improving company performance is multifaceted by adopting a qualitative descriptive method. Through a qualitative descriptive methodological approach based on literature review, content analysis, triangulation, and synthesis, the researcher was able to extract relevant information from the literature, organize the findings in a coherent framework, and provide meaningful interpretations for the academic community and business practitioners. The results of the research reveal that the role of managers in improving company performance is very significant. Managers act as leaders, planners, decision makers, facilitators, liaisons, mentors, and change agents